Getting God Out of Our (Modal) Business - Hanrahan, Rebecca (Sophia, 2009)
Some hold that if we can imagine God creating a world in which a particular proposition (p) is true, then we can conclude that p is possible. I argue that such appeals to God can’t provide us with a guide to possibility. For either God’s powers aren’t co-extensive with the possible or they are. And if they are, these appeals either beg the question or court a version of Euthyphro’s Dilemma. Some may argue that such appeals were only intended to prompt us to think broadly about the modal claim at issue. I argue instead that these appeals must be understood as more than mere prompts. For it is these appeals that would, if successful, render the conceivability principle viable.